Differential expression of programmed death 1 (PD-1) on various immune cells and its role in human leprosy - Mohammad Tarique; Huma Naz; Mohd Suhail; Mohd Suhail; Ali Turan; Chaman Saini; Naoshad Muhammad; Hari Shankar; Torki A. Zughaibi; Torki A. Zughaibi; Tabish H. Khan; Neena Khanna; et al. (Frontiers in Immunology, 2023)
Leprosy is a chronic bacterial disease caused by Mycobacterium leprae. Leprosy patients have been found to have defects in T cells activation, which is critical to the clearance of the bacilli. Treg cell suppression is mediated by inhibitory cytokines such as IL10, IL-35 and TGF-β and its frequency is higher in leprosy patients. Activation and overexpression of programmed death 1 (PD-1) receptor is considered to one of the pathways to inhibit T-cell response in human leprosy. In the current study we address the effect of PD-1 on Tregs function and its immuno-suppressive function in leprosy patients. Flow cytometry was used to evaluate the expression of PD-1 and its ligands on various immune cells T cells, B cells, Tregs and monocytes. We observed higher expression of PD-1 on Tregs is associated with lower production of IL-10 in leprosy patients. PD-1 ligands on T cells, B cells, Tregs and monocytes found to be higher in the leprosy patients as compared to healthy controls. Furthermore, in vitro blocking of PD-1 restores the Tregs mediated suppression of Teff and increase secretion of immunosuppressive cytokine IL-10. Moreover, overexpression of PD-1 positively correlates with disease severity as well as Bacteriological Index (BI) among leprosy patients. Collectively, our data suggested that PD-1 overexpression on various immune cells is associated with disease severity in human leprosy. Manipulation and inhibition of PD-1 signaling pathway on Tregs alter and restore the Treg cell suppression activity in leprosy patients.